Thank you for the opportunity to help you with your question!

11) if h(x) is even then h(-x) = h(x)

if g(x) is odd, then g(-x) = -g(x)

f(x) = g(x)*h(x)

f(-x) = g(-x) * h(-x)

f(-x) = -g(x) * h(x) (based on above)

f(-x) = -f(x). Thus, odd

13) Let g(x) and h(x) be arbitrary odd functions

this means that g(-x) = -g(x) and h(-x) = -h(x)

Let f(x) = g(x) + h(x)

f(-x) = g(-x) + h(-x)

f(-x) = -g(x) - h(x)

f(-x) = -(g(x) + h(x))

f(-x) = -f(x)

QED

14)There are plenty of functions that are not even or odd. For example, consider a function that is the sum of an even and odd function. It is neither odd nor even.

15) Even means that it is reflective over y-axis. Odd means it is reflective over origin.

Please let me know if you need any clarification. I'm always happy to answer your questions.